Health Service Providers’ Behaviors toward Youth Clients - Khanal, Shanti Prasad (Journal of Health Promotion, 2018)
This study has attempted to assess the behavior of health service providers during delivering the services to school and college going youths. The study followed the descriptive study design and it was based on quantitative data. The study utilized self administrated questionnaire for 249 college and school going youths aged 10 to 24 of secondary level in Surkhet valley. The study applied simple random sampling strategy to select the participants from selected area. The researcher determined the sample size by using Raosoft Sample Size Calculator. It was found that about one-third (36.94%) of the total recruited youths had utilized YFRH services. It was also found that 60% of them who had utilized the services reflected that the service providers were not friendly and welcoming. Forty percent youths noted that the service providers were judgmental and unfriendly. Almost all participants indicated that young people usually come to the service provider with considerable fear, often with worry about privacy and confidentiality. Majority (54.35%) of youths claimed that operating time of the service was inconvenient. Majority reported that the time spent by the service provider was very short and waiting time to meet the providers was too long. Majority (51.08%) reported that the time spent by the providers was very short. This study concludes that the behavior of the service provider seems unfriendly and unwelcoming for youth clients. This constitutes key deterrents to care seeking and the violations the human right. Addressing the service provider behaviors is, therefore, critical and significant.Journal of Health Promotion Vol.6 2008, p.60-69